Physical Activity and Lifestyle of the Elderly - Alicja Drohomirecka; Katarzyna Kotarska; Maria Makris (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
Systematic physical activity leads to some physical and psychological benefits for the body, and therefore, it is considered to be best practice in the prevention of public health. This statement is particularly important in the case of the elderly, as regular, individually-designed exercises, give way to an active lifestyle, which is important in the light of the increasing number of the elderly in Poland. The study aimed to evaluate physical activity of University of the Third Age students. The research material consisted of 73 people aged 60–74. Utilized in the study was a diagnostic survey method, with a specially-designed survey questionnaire constituted of 20 questions referring to pro-health lifestyle and physical activity of the subjected group. Based on the results analysis, it was concluded that the subjected elderly lead a healthy lifestyle and systematically undertake physical activity, which seems to be a very positive tendency.